EVALUASI PENGENDALIAN INTERN SISTEM PENAGIHAN PIUTANG - Risalatin, Nur Yulia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to evaluateaccounts receivable billing system at PT Pangan Mitra Sejahtera. The result of this research indicates that there are a lot of customers have exceeding the time limit of accounts receivable billing which has been specified by the company that is two weeks. The information system at PT Pangan Mitra Sejahtera indicates the weakness of protection and the division which is responsible for checking the due date of accounts receivable. The impact which iscaused by this weaknessis the account receivables which have not been collectedthen are stacking up in large quantities and in a long period of time. The alternative way to solve the account receivables whichexceed the repayment of the time limit by reducing the purchasing discount and to acceleratethe repayments of account receivables is by giving the bank a guarantee to the company which will make thecompany easy to get the payment from the customers. Keywords: Billing system, Internal Control , Payment Limits, Fine for late.